Analysis of Factors Associated with Exclusive Breastfeeding at BPM Ambarita, Humbang Hasundutan District - Martaulina Sinaga (Science Midwifery, 2021)
Exclusive breastfeeding is breastfeeding from the time the child is born until the child is 6 months old. Exclusive breastfeeding until6 months can meet the needs of children, over the age of 6 months new children need additional food. This study aims to determine the analysis of fassociated actorExclusive breastfeeding at BPM Ambarita, Humbang Hasundutan District.Method: This type of research is descriptive analytic with a cross sectional approach which aims to explain the analysis of factors related to exclusive breastfeeding in BPM Ambarita Humbang Hasundutan District. The population in this study were all babies who were brought to visit BPM Ambarita, Humbang Hasundutan District, and the samples were taken using a total sampling technique, where the entire population was used as a sample, totaling 85 mothers at BPM Ambarita, Humbang Hasundutan Regency. Data analysis technique using the chi square statistical test and Fisher's Exact test Results: There is a relationship between age, parity, knowledge, attitudes and exclusive breastfeeding in BPM Ambarita, Humbang Hasundutan District. There is no relationship between education, work, income by exclusive breastfeeding at BPM Ambarita Humbang Hasundutan District. It is recommended to increase information to the wider community about exclusive breastfeeding through counseling, dissemination of printed media such as leaflets regarding the benefits of breastfeeding, as well as the advantages of breastfeeding both for mothers in labor and pregnant women